2019
DOI: 10.1016/j.fbp.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of tomato by-products’ bioactive compounds using ohmic technology

Abstract: Tomato by-products Ohmic heating Extraction optimization By-products valorization New extraction method Polyphenols Carotenoids a b s t r a c tTomato peels and seeds are the main by-products of the tomato industry and represent an interesting source of bioactive compounds (BC) including carotenoids, which can be then used as colorant to commercial aquaculture. The aim of the present work was to optimize the extraction of BC from tomato by-products using Ohmic heating (OH) technology. OH extraction experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 46 publications
2
76
1
1
Order By: Relevance
“…USA), using a UV-vis photodiode array detector. The absorption spectra were recorded between 212 and 720 nanometers (Coelho et al, 2019). A Symmetry ® C18 column (250 × 4.6 mm, 5 m, Agilent, USA) was used as the stationary phase.…”
Section: Anthocyanins Analysis By Hplcmentioning
confidence: 99%
See 1 more Smart Citation
“…USA), using a UV-vis photodiode array detector. The absorption spectra were recorded between 212 and 720 nanometers (Coelho et al, 2019). A Symmetry ® C18 column (250 × 4.6 mm, 5 m, Agilent, USA) was used as the stationary phase.…”
Section: Anthocyanins Analysis By Hplcmentioning
confidence: 99%
“…OH has been successfully used for thermal processing of foods (i.e. blanching, pasteurization, sterilization) (Jaeger et al, 2016;Pereira et al, 2016;Coelho et al, 2019). This energy efficiency can be achieved because OH is capable of a precise control of the temperature allowing volumetric HTST process avoiding contact with hot surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…OH is an environmentally friendlier and more efficient thermal technology than traditional methods currently used in food processing; in OH, an electric current is passed directly through materials having electrical resistance, generating heat and increasing the instantaneous and homogeneous temperature inside the product (Coelho et al, 2019;Pereira et al, 2016). This technology has an energy efficiency of over 90% and, when compared to the conventional thermal method, which is less efficient, can achieve energy savings of up to 70% (Rocha et al, 2018).…”
Section: Ohmic Heatingmentioning
confidence: 99%
“…Currently, the "green extraction" alternatives have been increasingly studied and implemented without the need for "clean-up" processes to recover the compounds that may be safely and immediately consumed or further used in the manufactured of foods (Bursać Kovačević et al, 2018;Deng et al, 2015). Numerous authors have suggested the alternative extraction methods, such as ultrasonic, microwaves, electrical technologies (pulsed electric fields, high electric discharges, and ohmic heating) and mechanical treatment (pressurized hot water extraction and subcritical fluid extraction) (Coelho, Pereira, Rodrigues, Teixeira, & Pintado, 2019;Deng et al, 2015;Galanakis, 2012Galanakis, , 2015aGalanakis, Tsatalas, Charalambous, & Galanakis, 2018;Kalli, Lappa, Bouchagier, Tarantilis, & Skotti, 2018). These are processes suitable for the improved recovery of valuable compounds since they use green solvents and reduce solvent consumption, and at the same time, they facilitate the plant cell disruption and compounds extraction, minimizing the impact on the BCs (Barba, Zhu, Koubaa, Sant'Ana, & Orlien, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have used vacuum pulsing (Martins et al, 2019), ohmic heating (Coelho et al, 2019), electrodialysis (Xue et al, 2018), high pressure (Shinwari and Rao, 2018), microwave (Leonelli and Mason, 2010), and high-power ultrasound (Polachini et al, 2019;Goula et al, 2017), in order to accelerate mass transfer rates. Ultrasound is a promising emerging technology in the food processing industry, as it is innovative, achieving important results generally complementary to classical techniques, such as salting (Sharma and Dash, 2019).…”
Section: Introductionmentioning
confidence: 99%